Generating a self-organizing fuzzy controller from human skill performance for multivariable systems - Lekova, Anna; Boyadjiev, Dimebo (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a learning concept for creating of a self-organizing fuzzy controller for multi variable systems by explicit use of human skill performance during the control of a complex technological process. When such processes cannot be entirely controlled automatically, a natural way to achieve flexible and adaptive control is a combination of human resources and information technologies. The main idea is the decomposition of a multivariable control system into several subsystems with two inputs and multiple outputs.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka